(untitled) (Revista de Educação Pública, 2013)
Intencionamos no presente trabalho problematizar e tentar responder à indagação: como o professor se torna professor? Por meio de pesquisas desenvolvidas em ambientes narrativos, na forma de um dispositivo de modalidade (auto)biográfica: os Ateliês Biográficos de Projeto (ABP), proporcionamos meios para a emancipação profissional docente. As possibilidades que o sujeito/professor tem de biografar-se, a biograficidade (DELORY-MOMBERGER, 2005), supõem que o sujeito, ao narrar, ao mesmo tempo distancia-se e interpreta a si, por meio da identificação de forças mobilizadoras que resultam em projetos, levando-os a apropriação das experiências, reforçando o poder de formação (PINEAU, 1983) de ações dessa natureza. Abstract This work has the intention to ask the following question and try to give some answers: How the teacher becomes a teacher? We developped researches in ambiances of autobiographical narratives, such as project biografical workshops with the purpose to promote the teacher’s profissional emancipation. The possibilities of the subject/teacher to biograph himself, the biographicity (DELORY-MOMBERGER, 2005), suppose that the subject, during the narrative, build a distance and, at the same time, interpret himself when he identificates the forces that moves him towards his projects. This is the way to be aware of the experiences that improve the power of formation (PINEAU, 1983) of such actions. Keywords:Teacher’s life history. Project Biographical Workshops.Teacher’s professional emancipation.